2013
DOI: 10.3389/fnins.2013.00166
|View full text |Cite
|
Sign up to set email alerts
|

Teneurin C-terminal associated peptides (TCAP): modulators of corticotropin-releasing factor (CRF) physiology and behavior

Abstract: The existence of the teneurin C-terminal associated peptides (TCAP) was reported in 2004 after screening a rainbow trout hypothalamic cDNA for corticotropin-releasing factor (CRF)-related homologs. In vertebrates, there are four TCAP paralogs, where each peptide is associated with a teneurin transmembrane protein. The TCAPs are 40 or 41 amino acids in length and possess less than 20% residue identity with the CRF family of paralogs. Orthologs of TCAP are found in all metazoans with the possible exception of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
(86 reference statements)
0
14
1
Order By: Relevance
“…MS analysis of the native Lasso fragments (Figure 7E ) revealed a large number of peptides from the ectodomain, including the peptide (MW 3469.95, see above) localized immediately downstream of the S1 (furin) site, but no peptides from the other Lasso domains. Two tryptic peptides were found within the sequence corresponding to TCAP, which indicated that at least the larger of the two NF (NF268) was not cleaved at the C-terminus, contrary to what was proposed previously for teneurin-2 (Chen et al, 2013 ).…”
Section: Resultscontrasting
confidence: 88%
“…MS analysis of the native Lasso fragments (Figure 7E ) revealed a large number of peptides from the ectodomain, including the peptide (MW 3469.95, see above) localized immediately downstream of the S1 (furin) site, but no peptides from the other Lasso domains. Two tryptic peptides were found within the sequence corresponding to TCAP, which indicated that at least the larger of the two NF (NF268) was not cleaved at the C-terminus, contrary to what was proposed previously for teneurin-2 (Chen et al, 2013 ).…”
Section: Resultscontrasting
confidence: 88%
“…Application of the Teneurin-2 C-terminus in hippocampal culture induces presynaptic Ca 2+ signaling (Silva et al, 2011 ). This is reminiscent of the Teneurin C-terminal associated peptide (TCAP), a 41-residue peptide that can be liberated and is thought to regulate stress response, dendritic remodeling in the hippocampus, BDNF levels, and corticotropin-releasing factor signaling (Rotzinger et al, 2010 ; Ng et al, 2012 ; Tan et al, 2012 ; Chen et al, 2013 ). Indeed, Teneurin-2 can be cleaved in culture (Silva et al, 2011 ), supporting this model but could also function by another, unknown mechanism.…”
Section: Synaptic Teneurins In Vertebrate Systemsmentioning
confidence: 99%
“…In their contribution, Chen et al (2013) examine the evolutionary origins of the tenuerin C-terminal associated peptides (TCAP), peptides which may have predated the origin of the CRF peptide family. Chen et al (2013) review data on the neuromodulatory actions of TCAP-1 and both its direct and indirect effects as an indirect modulator of CRF intracellular signaling.…”
Section: Citationmentioning
confidence: 99%
“…In their contribution, Chen et al (2013) examine the evolutionary origins of the tenuerin C-terminal associated peptides (TCAP), peptides which may have predated the origin of the CRF peptide family. Chen et al (2013) review data on the neuromodulatory actions of TCAP-1 and both its direct and indirect effects as an indirect modulator of CRF intracellular signaling.Feeding and intake of nutrients is essential for the success of any species. A stress-response, as regulated by the CRF family of peptides, generally has suppressive actions on appetite and digestion in order to shunt energy from a parasympathetic need to arousal and sympathetic requirements.…”
mentioning
confidence: 99%